R&D and Foreign Sales in Multinationals: A Simultaneous Relationship? - Gunnar Fors; Roger Svensson (The Research Institute of Industrial Economics (IUI), 1996)
This paper analyzes the simultaneous relationship between R&D and foreign sales in Swedish multinational enterprises in the manufacturing sector. We argue that this two-way relationship should especially apply to multinationals based in small open economies due to the firms' high dependence on foreign markets. The only previous study addressing this issue used data on multinationals originating from the United States, a country with a large domestic market, and it did not find evidence of the hypothesized simultaneous relationship. Our empirical results suggest a positive and significant effect in both directions.
Keywords: F23; O32; 330; R&D; Foreign Sales; Multinational Enterprises; Industrieforschung; Multinationales Unternehmen; Technologietransfer; Internationales Marketing; Schweden